2016
DOI: 10.1186/s12884-016-1078-6
|View full text |Cite
|
Sign up to set email alerts
|

Concerns, attitudes, beliefs and information seeking practices with respect to nutrition-related issues: a qualitative study in French pregnant women

Abstract: BackgroundFrom a life course perspective, pregnancy leads to a rise in nutrition awareness and an increase in information flow in favour of adopting healthier eating behaviours. This qualitative study was designed to better understand the determinants of eating behaviours in French pregnant women by focusing on their concerns, attitudes and beliefs and their nutrition-related information seeking practices.MethodsSeven focus groups were conducted, involving a total of 40 French pregnant women. An inductive them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
56
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 44 publications
(88 reference statements)
13
56
1
1
Order By: Relevance
“…Pregnant women in this study modified their food choices, by eating less fruits and vegetables and more convenience items, due to physiological changes, pregnancy-related symptoms, or the behavior of their partners, which is consistent with previous studies (Bianchi et al, 2016;Goodrich et al, 2013;Graham et al, 2013;Hromi-Fiedler et al, 2016;Lucas et al, 2016;Reyes et al, 2013). The results showed that mothers who lived with a spouse were affected by their spouses' healthy and unhealthy behaviors and vice versa.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Pregnant women in this study modified their food choices, by eating less fruits and vegetables and more convenience items, due to physiological changes, pregnancy-related symptoms, or the behavior of their partners, which is consistent with previous studies (Bianchi et al, 2016;Goodrich et al, 2013;Graham et al, 2013;Hromi-Fiedler et al, 2016;Lucas et al, 2016;Reyes et al, 2013). The results showed that mothers who lived with a spouse were affected by their spouses' healthy and unhealthy behaviors and vice versa.…”
Section: Discussionsupporting
confidence: 90%
“…High social support from a partner is one factor that could enhance prenatal intake of produce (fruits and vegetables) if these foods are eaten together, or the knowledge of how to cook these foods is exchanged (Goodrich et al, 2013;Hromi-Fiedler et al, 2016). Indeed, women have been reported to be more receptive to cooking knowledge when it comes from a family member (Bianchi et al, 2016). This is because human behavior is influenced by one's partner; for example, pregnant women feel self-conscious about unhealthy eating habits when their partners witness these habits (Graham et al, 2013).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Our results support and extend the results from the USA [26] in which researchers conducted interviews with 24 overweight and obese women and found that discussions about GWG with HCPs did not occur but that women would like to have these discussions. Focus groups with pregnant women in France also noted that women look to their HCP for direction about health, eating and appropriate weight gain [27]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the population sizes were generally small (n = 17-60) [8,12,13,18,20,23], and information sources were rarely the main outcome [8,12,16,[19][20][21][22][23]. Three studies had moderate methodological quality and sufficient population sizes (n = 350-368) [7,9,24].…”
Section: Introductionmentioning
confidence: 99%